Corporate Social Responsibility Reporting and Accountability‎Toward Sustainability: A Qualitative Study at Hotel YusraFrom ‎An Islamic Accounting Perspective - Anisah, Nur; Sukoharsono, Eko Ganis; Roekhuddin; Iqbal, Syaiful (International Journal of Accounting and Economics Studies, 2026)
This study aims to explore and interpret corporate social responsibility (CSR) reporting and accountability practices toward sustainability at ‎Hotel Yusro, a sharia-based hotel in Indonesia, from an Islamic accounting perspective. This research employs a qualitative approach using ‎an interpretive paradigm. Data were collected through participatory observations, in-depth interviews with key informants involved in CSR ‎implementation and financial management, and analysis of CSR-related documents and reports. The data were analysed using triangulation ‎techniques to ensure validity and reliability. The findings indicate that CSR practices at Hotel Yusro are implemented based on Islamic ‎values and demonstrate convergence with conventional CSR typologies, particularly in the dimensions of economic, social, and ‎environmental accountability. Islamic values enrich CSR practices by strengthening accountability mechanisms, especially in CSR budgeting, ‎reporting, and disclosure, positioning CSR not only as a business strategy but also as a form of ethical responsibility. The study also finds ‎that CSR expenditures are recognised as operating expenses and managed through internal reporting mechanisms that reflect transparency ‎and responsibility toward stakeholders. This study contributes to the development of accounting science, particularly in the field of CSR ‎reporting and accountability toward sustainability within Islamic-oriented hospitality organisations. The findings provide empirical insights ‎into how Islamic accounting values can strengthen sustainability-oriented accountability practices in the hospitality sector.
Keywords: Corporate Social Responsibility; Sustainability; Accountability; CSR Reporting; Islamic Accounting; Sharia Hotel